(untitled) (Perspektiven - Soziale Arbeit in der Migrationsgesellschaft und muslimische Wohlfahrtspflege, 2024)
In their introduction to this special issue on "Volunteering in the context of flight and asylum - Empirical insights into (educational) practice", Fenna tom Dieck and Lisa Rosen outline the research field in Germany with a special focus on qualitative studies. They conclude that future research can benefit from the further development of multi-perspective approaches, e.g. that the inclusion of different stakeholder perspectives can facilitate the decentering of researchers’ perspectives.